Detection and mitigation of collusive interest flooding attack on content centric networking. (3rd December 2019) - Shigeyasu, Tetsuya; Sonoda, Ayaka
According to the development of Information and Communications Technology (ICT), deployments of consumer devices, such as note PC, smartphone, and other information devices, give users easy access to the internet. Users having these devices use services of e-mail, Social Network Service (SNS). The Named Data Networking (NDN) which is the most popular network architecture has been proposed to realise the concept of content centric network (CCN). However, it has been also reported that the NDN is vulnerable to Collusive Interest Flooding Attack (CIFA). In this paper, we propose a novel distributed algorithm for detecting CIFA while keeping availabilities of NDN. The results of computer simulations confirm that our proposal can detect and mitigate the effects of CIFA, effectively.